Peningkatan Perilaku Personal Hygiene Genital Dengan Metode Storytelling - Liza Eri Widyawati; Reni Wahyu Triningsih; Didien Ika Setyarini (Malang Journal of Midwifery (MAJORY), 2019)
Genital personal hygine is an important part because if a girl is not enough to maintain the cleanliness of her reproductive organs, there is a risk of infection in the reproductive organs. The introduction of personal hygiene needs to be given starting early, one of them with the storytelling method. The purpose of this study was to determine personal hygiene behavior before and after storytelling was given. The method used is a one group pretest-post test. Respondents in this study were 34 female students at SDN Junrejo 01 Batu, selected by purposive sampling. Data collected using a questionnaire that has been designed to test its validity and reliability. The results showed that before storytelling 64.7% of students had behaviors in the poor category and 35.3% in the moderate category. After storytelling, 70.6% of students had behaviors in the category and 26.5% were in the moderate category, and 3% in the poor category. The results of statistical analysis using the Wilcoxon signed rank test showed p value <0.001 which means that there is an influence of the storytelling method on the increase in personal genital hygiene behavior at SDN Junrejo 01 Batu. Provision of health education needs to be done by health workers periodically as an effort to promote reproductive health in adolescents so that adolescents can behave properly in maintaining reproductive health. Keywords: Storytelling, Adolescent Behavior, Genital Personal Hygiene